Work-Related Self-Directed Learning as Basis towards Cultivating the Five Disciplines of Learning Organization by Senge - Ida Juliana, Hutasuhut; Shahren, Ahmad Zaidi Adruce; Sopian, Bujang; Hasbee, Hj Usop (2017)
This study aims to provide evidence on how work-related self-directed learning (WRSDL) practices among staffs and managers from various job fields proof as basis towards cultivation of the Five Disciplines of Learning Organization by Senge. This qualitative study was conducted in a prominent motorcycle-manufacturing company in Indonesia that intentionally set the organizational direction toward a learning organization. In this organization, improvement and innovation have always been the central issues and become a way of life ingrained among employees. A total of thirty staffs and managers who were prominent as self-directed learners were purposively interviewed using semi-structured interview technique. These participants were selected in order to get their experience in carrying out learning in the workplace context. The data gathered were analyzed using content analysis approach. This study provides evidences that cultivating WRSDL will strengthen the implementation of the five disciplines of learning organization. This study contributes insight of the importance of WRSDL to the body of knowledge, and suggested recommendation to practitioner as well as for future research which will be explained later.